Gesture Recognition For Human-Computer Interaction - Shivaprasad Satla ,Syed Shareefunnisa,K.V Subramanyam Chavva RaviKishore Reddy (International Journal of Advanced Science and Technology, 2020)
We know that our future completely depends on robots, so Human-Computer Interaction (HCI) plays a major role in communication with the systems. By this normal people can easily communicate with the system but in case of dumb HCI has no support. In this case, gestures are more useful to communicate with systems. Gesture is a type of non-verbal correspondence in which visible body activities impart a specific message motion incorporating hands, face, and different pieces of the body. In our proposed work, detection and recognition of hand gestures using various Learning algorithms are used. GR is one of the significant procedures to fabricate well-disposed interfaces. For instance, a robot that can perceive hand motion can take orders from people, and for the individuals who can’t talk or hear, this innovation is helpful.